Intergovernmental grants and financial autonomy under asymmetric information - Katharina Herold (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2009)
This paper analyses and compares the efficiency of alternative incentive compatible grant schemes under asymmetric information relieving subnational governments of excessive debt burden. They allow intervention into local debt, local tax or complete local fiscal policy. In the first case, separation of types can be induced by forcing recipients to inefficient high borrowing and in the second case by imposing inefficient high tax rates. In the last case, fiscal policy of the recipient region is distorted in the period of the exogenous shock. We show that constraining complete financial autonomy leads to the lowest welfare losses. This is due to the fact that complete regulation of local fiscal policy reduces the incentive of contributing local governments to defect from truthful relevation.
Keywords: H74; H77; D82; 330; vertical transfers; subnational debt; asymmetric information adverse selection; financial autonomy; Finanzausgleich; Finanzföderalismus; Öffentliche Schulden; Finanzpolitik; Teilstaat; Asymmetrische Information; Adverse Selection; Selbstverwaltung; Wohlfahrtseffekt; Theorie